Effect the Temperature on Structure and Optical Properties for ZnS nanostructure Thin Film - Abbas, Nada K.; Al- Rasoul, Khalid T.; Shanan, Zainb J. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
ZnS nanocrystalline thin films by different temperature of reaction were prepared by chemical bath deposition using thiourea and zinc acetate as S2– and Zn2+ source. The optical absorption studies in the wavelength range 200–1100 nm show that band gap energy of samples 3.75 and 4.0 eV for different temperature reaction condition. The refractive index was estimated within the visible wavelength at 623 nm, it was 2.04 for sample 1 and its value will increase for sample 2 to be 2.55. The room temperature photoluminescence spectra of the films showed two peaks for all samples. We assigned the first peak due to band gap transitions while the latter was due to zinc vacancy in the films. Structural analysis using atomic force microscopy shows that the grain size for films were 73.2 and 87.34 nm. X-ray diffraction analysis indicates that both of them formed in the reaction bath have cubic zinc blende structure .The structural estimation shows variation in grain size 7nm and 20nm with different temperature reaction.